"Knowledge is like food": qanruyutet on change and subsistence from John Smith. Issue 1 (3rd April 2021) - Smith, John; Gleason, Sean
ABSTRACT: Yup'ik Elder John Smith (Hooper Bay) recounts wise words ( qanruyutet ) about growing up during a time of rapid change in the Yukon-Kuskokwim (Y-K) Delta. His oral histories include instructions ( alerquutet ), prohibitions ( inerquutet ), and cautionary tales ( neq'ayarat ) regarding Yup'ik subsistence practices known collectively as Yuuyaraq . Taken together, these oral histories, represent a genre of performance sometimes overlooked in contemporary scholarship that explores the role that modernization and outside contact have on indigenous subsistence practices. While John's qanruyutet discuss the plants, species, and practices of the Y-K Delta, his words – meant to be read aloud – also provide valuable insight for individuals interested in animal-human relations and posthuman performance.